Interannual and daily activity patterns of mid-sized mammals in Maracaibo Lake Basin, Venezuela - Morán, Lisandro; García, Luis; Ferrebuz, José D.; Sánchez, Roxana; Porta, Alberto; Sánchez-Mercado, Ada; Ferrer-Paris, José Rafael (THERYA, 2018)
Despite its biogeographic importance, the mammals of Maracaibo lake basin have been poorly studied. The objectives of this study were to: 1) provide a list of the mammal species detected by combining information from camera traps and other sources, and 2) describe diurnal and annual activity patterns for some of the species detected. Camera-trapping was carried out for one year in five localities within the Burro Negro Protection Zone (Spanish acronym ZPBN). Records of terrestrial mammals (excluding Chiroptera) were compiled from: 1) direct and indirect opportunistic records during field visits, 2) informal interviews with local inhabitants, 3) three national natural history collections, and 4) scientific literature. The complementarity between sources, similarity with other localities within the region, and temporal changes in composition were evaluated with the Sørensen Similarity Index (RS), and annual differences in the number of detections per sampling effort were evaluated using a X2 test. Sampling effort was 1,799 camera days, resulting in 569 events of mammal detection recorded and 20 species from 17 families in 9 orders identified. Four species (Dasypus novemcinctus, Dasyprocta leporina, Cerdocyon thous and Leopardus pardalis) were captured all year round. Camera traps detected half of the non-flying mammal species in the area, including five that had not been previously reported by other sources (Cuniculus paca, Coendou prehensilis, Sylvilagus floridanus, Procyon cancrivorus and Puma yagouaroundi). At least three species (Panthera onca, Odocoileus virginianus, and Hydrochoerus hydrochaeris) had been reported as historically abundant, but were not detected during the year of camera trapping, which could be due to recent declines in their populations. Camera trapping provides reliable records on the presence of four species with data gaps in their distribution ranges (Myrmecophaga tetradactyla, Coendou prehensilis, Cerdocyon thous and Procyon cancrivorus), as well as baseline data for evaluating the distribution overlap between pairs of species, such as Tamandua mexicana and T. tetradactyla, and Dasyprocta leporina and D. punctata. A higher species richness was observed between June and August, in the rainy season.